AGO recommendations for the diagnosis and treatment of patients with early breast cancer: update 2025 - Park-Simon, Tjoung-Won; Müller, Volkmar; Albert, Ute-Susann; Banys-Paluchowski, Maggie; Bartsch, Rupert; Bauerfeind, Ingo; Bjelic-Radisic, Vesna; Blohmer, Jens-Uwe; Budach, Wilfried; Dall, Peter; Ditsch, Nina; Fallenberg, Eva M.; et al. (Breast care, 2025)
The Breast Committee of the Arbeitsgemeinschaft Gynäkologische Onkologie (German Gynecological Oncology Group, AGO) presents the 2025 update of the evidence-based recommendations for the diagnosis and treatment of patients with early breast cancer.
Online veröffentlicht: 8.März 2025
Gesehen am 16.09.2025